Pengaruh Penetapan Harga, Brand Image, Kualitas Pelayanan, Dan Promosi Terhadap Keputusan Pembelian Pengguna Jasa Ekspedisi JNE Cabang Bantul - Rokhim, Abdul; Fuady, Misbach (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to analyze the influence of pricing, Brand Image, service quality, and promotion on consumer purchasing decisions at JNE Bantul Branch Courier Services. The population of this study was consumers of JNE Bantul Branch, with sampling using the non-probability sampling method, precisely the accidental sampling technique. Data analysis was carried out using multiple linear regression. The results of the study showed that the variables of Pricing, Service Quality, and Promotion did not affect Purchasing Decisions. While Brand Image has a positive effect on purchasing decisions. The value of Adjusted R is 0.288, indicating that 28.8% of purchasing decisions can be explained by the independent variable Brand Image. While the remaining 71.2% is explained by other causes that are not examined in this study and are not the variables of Pricing, Service Quality, and Promotion. Which means that these three variables are not important concerns/considerations for customers.